CHEMICAL COMPOSITION OF PECULIAR STAR HD91375 – THE MEMBER OF SIRIUS MOVING GROUP - Yushchenko, V. (Одеські астрономічні публікації, 2009)
We present the results of determinations of the abundances of chemical elements in the atmosphere of hot chemically peculiar star HD91375 – member of Sirius moving group. We used the observations made at 8.2 meter ESO telescope. The abundance pattern of HD91375 is found for the first time, the comparison with the abundances of Sirius~A is made. The abundance patterns of Sirius and HD91375 are clearly different. It confirms the possibility of recent accretion event in the Sirius binary system.